Effect of chitosan-gelatin coating containing nano-encapsulated tarragon essential oil on the preservation of pork slices. (August 2020) - Zhang, Huiyun; Liang, Ying; Li, Xinling; Kang, Huaibin
Abstract: There is an increasing demand for bio-based packaging materials incorporated with active nanoparticles as one of the new technologies to obtain food products with improved quality and extended shelf-life. The objectives of this study were to develop a chitosan-gelatin based edible coating incorporated with nano-encapsulated tarragon essential oils (TEO) and to investigate the effects of chitosan-gelatin coatings containing TEO or TEO-loaded nanoparticles (TEO-NPs) on the preservation of pork slices during refrigerated storage for 16 days. Nanoparticles with the average diameters of 246.27–504.60 nm were produced using different mass ratios of chitosan to TEO (1:0, 1:0.2, 1:0.4, 1:0.6, 1:0.8 and 1:1) by ionic gelation method. Zeta potential and encapsulation efficiency (EE) of the prepared TEO-NPs were 27.07–37.12 mV and 9.83–35.57%, respectively. TEO-NPs with the maximum EE were applied for preparing the edible coatings. The results suggested that the coating treatments could significantly inhibit quality deterioration of pork slices. Nano-encapsulation contributed to the sustained release of TEO and caused an improved antioxidant, antibacterial and sensory properties. The study suggests that chitosan-gelatin coating incorporated with TEO-NPs could be developed as a prospective active packaging to preserve pork slices. Highlights: Tarragon essential oil (TEO) loaded nanoparticles were prepared. Pork slice was coated with chitosan-gelatin coating containing free or encapsulated TEO. Coating inhibited lipid oxidation, microbial growth, and improved sensory attributes. Chitosan-gelatin coating containing encapsulated TEO showed the best performance on meat preservation.